Dengue virus downregulates TNFR1- and TLR3-stimulated NF-κB activation by targeting RIPK1 - Udawatte, Darshika J.; Lang, Diane M.; Currier, Jeffrey R.; Medin, Carey L.; Rothman, Alan L. (Frontiers in Cellular and Infection Microbiology, 2022)
Dengue virus (DENV) infection is the most prevalent arthropod-borne virus disease and is endemic in more than 100 countries. Several DENV proteins have been shown to target crucial human host proteins to evade innate immune responses and establish a productive infection. Here we report that the DENV NS3 protein targets RIPK1 (Receptor Interacting Protein Kinase I), a central mediator of inflammation and cell death, and decreases intracellular RIPK1 levels during DENV infection. The interaction of NS3 with RIPK1 results in the inhibition of NF-kappaB activation in response to TNFR or TLR3 stimulation. Also, we observed that the effects of NS3 on RIPK1 were independent of NS3 protease activity. Our data demonstrate a novel mechanism by which DENV suppresses normal cellular functions to evade host innate immune responses.